Stereotypes concerning the phenomenon of violence in the contemporary Polish family - Małgorzata Herudzińska (Studia z Teorii Wychowania)
The purpose of the article is to try to answer the general question about stereotypes regarding violence in the contemporary Polish family. The following specific questions arise: How is domestic violence understood? What types of violence can be distinguished? What are the effects of violence? Who is most often affected by violence? What stereotypes about domestic violence function in the social consciousness? For example: One of the stereotypes functioning in our society is the conviction that domestic violence primarily affects a family with a worse financial situation or a lower educational status. Whereas, therapists have often paid attention [...] to the fact that with the increase in education, the probability of using domestic violence is not reduced, but the forms become more sophisticated." (Muszyński 2008, s. 12).In order to answer the abovementioned questions, the existing data and the results of Author’s own research will be used.